Beyond borders : notes on the colonial and post-colonial dynamics in the Americas, Europe and Indonesia / Baskara T. Wardaya - Baskara T. Wardaya SJ (Sanata Dharma University Press, 2017)
xviii, 228 halaman : ilustrasi ; 23 cm